Synthesizing high-density U₃O₈ powder from UO₂F₂ solution via AUC precipitation - Nguyen, Trong Hung; Nguyen , Thanh Thuy (Nuclear Science and Technology, 2026)
Uranium trioxide octaoxide compound - U3O8 is a crucial nuclear material in nuclear technology. It is used as nuclear fuel for research reactors. To achieve this goal, an important characteristic that U3O8 powder must possess is a density ranging from 88-98% of the theoretical density (TD). This paper reports the results of an investigation of the ammonium uranyl carbonate (AUC) precipitation from uranyl fluoride (UO2F2) solution and optimization of sintering parameters for synthesizing high-density U3O8 powder, meeting the specified standards for manufacturing dispersed nuclear fuel for research reactors. The AUC precipitation was conducted using uranyl fluoride (UO2F2) solutions with uranium concentrations ranging from 80 to 120 gL-1 and ammonium carbonate ((NH4)2CO3) concentrations as precipitant were maintained between 200 and 400 gL-1, while the (NH4)2CO3 to U (C/U) molar ratios were kept equal to or greater than 6. The investigated parameters for sintering of the high-density U3O8 nuclear material derived from AUC (ex-AUC U3O8) are the sintering temperature and time. The experimental studies are designed by using the Response Surface Methodology (RSM) based on a Central Composite Design (CCD). As a result, a regression equation describing the dependency of U3O8 powder density on sintering temperature and time has been established. Based on this equation, the sintering for synthesizing high-density U3O8 powder has been optimized. The regression equation aids in controlling the parameters of the U3O8 powder sintering